Performatividades da midiatização: as experimentações comunicacionais da drag Rita Von Hunty - Godoi, Rodrigo Duarte Bueno de (Universidade do Vale do Rio dos Sinos, 2025)
This research investigates the mediatization experiments produced by drag artists. It seeks to understand the ongoing process in which drag artists have transitioned from underground spaces to spaces of extreme visibility, particularly through experimental modes of media engagement and the management of social circulation processes of meanings. The empirical focus is on the practices of Rita Von Hunty, a highly visible celebrity drag queen in Brazil and the creator of the YouTube channel 'Tempero Drag.' Rita Von Hunty is the drag persona of the actor and language and literature teacher Guilherme Terreri de Lima Pereira. The research requires an understanding of the drag culture context as part of the case study because it is within this context that Guilherme is situated. Furthermore, like other cultural experiences, what Guilherme/Rita does also, in some way, challenges and transforms the context itself. Methodologically, the study is constructed as a mediatized case study, with a focus on the evidence paradigm, aiming not only to collect and select evidence but primarily to produce inferences about the practice’s logics. Empirical materials from different origins were analyzed, selected according to criteria outlined in the chapter dedicated to the case construction. The theoretical discussions engage with mediatization theories, with an emphasis on its Latin American approach, as well as discussions on performance, social fields, and celebrity studies. More specifically, Rita's practices suggest a confrontation of a context of misinformation and social invisibility. Finally, the investigated case allows for an understanding that the production of mediatized processes by drag artists operates as a tool of resistance against the material conditions of life and of circulation within culture.
Keywords: Midiatização; Drag-queens; Rita Von Hunty; Performance; Arte Drag; Mediatization; ACCNPQ::Ciências Sociais Aplicadas::Comunicação